Sociodemographic variables associated with knowledge regarding dengue Vector Control Among the Community of Tehsil Sahiwal, Sargodha - Aslam, Muhammad; Faridi, Tallat Anwar; Hameed, Sajid (Pakistan Journal of Health Sciences, 2021)
As dengue is a devastating disease, adequate steps by the community are essential for its control and prevention. Dengue fever is an important public health issue not only in Pakistan but also in developed countries. Insufficient basic infrastructure, rural-urban migration, water storage, rapid populace growth, and increase in solid waste volume. Objective: To access the knowledge of the community regarding dengue Vector Control and sociodemographic variables. Methods: The research was conducted in a community setting and was cross-sectional. The study took place in the Tehsil Sahiwal in the District of Sargodha. A total of 384 people took part in the study. Results: Among 384 respondents, 35 (9.1%) were government employees and majority (51.1%) were working in private firms while 153 (39.8%) respondent were housewives/jobless. Conclusion: Knowledge for dengue control program was found to be good (53.9%) in the selected population of Tehsil Sahiwal, Sargodha. However, people should be continued to be educated through television, newspapers, awareness campaigns.